2001
DOI: 10.1002/1521-3765(20010401)7:7<1431::aid-chem1431>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Remote Dipole Effects as a Means to Accelerate [Ru(amino alcohol)]-Catalyzed Transfer Hydrogenation of Ketones

Abstract: A new generation of 2-aza-norbornyl amino alcohol ligands for the catalytic transfer hydrogenation reaction of aromatic ketones was synthesized. Extremely active catalysts were formed by introducing a ketal functionality at the rear end of the ligand. Acetophenone was reduced in 96% ee at low catalyst loading, substrate to catalyst ratio, S/C 5000, within 90 minutes with isopropyl alcohol as the hydrogen donor. It was found that the dioxolane substituent in the ligand increased the turnover frequency, TOF50, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(43 citation statements)
references
References 23 publications
0
43
0
Order By: Relevance
“…To date, the most efficient and enantioselective catalysts for this reaction are based on ruthenium and rhodium 2. 3 They catalyze the asymmetric hydrogenation of acetophenone near room temperature with the highest turnover frequencies (TOFs) in the range 100–4000 h −1 4. Iron‐based catalysts of comparable activity would be desirable owing to their potentially lower cost, toxicity, and environmental impact.…”
Section: Methodsmentioning
confidence: 99%
“…To date, the most efficient and enantioselective catalysts for this reaction are based on ruthenium and rhodium 2. 3 They catalyze the asymmetric hydrogenation of acetophenone near room temperature with the highest turnover frequencies (TOFs) in the range 100–4000 h −1 4. Iron‐based catalysts of comparable activity would be desirable owing to their potentially lower cost, toxicity, and environmental impact.…”
Section: Methodsmentioning
confidence: 99%
“…Mechanistic studies on non-TIQ related ligands [1,3] developed by Noyori have demonstrated that typically two stereogenic centers, a cyclic secondary amine and a secondary alcohol is required for optimal chiral activity. [16][17][18] For maximum activity these two metal coordination sites are typically within three bonds of each other. In this paper, we introduce the tetrahydroisoquinoline (TIQ) ligands which have initially a single chiral centre, a secondary amine in a six memembered ring with a primary alcohol as a side chain.…”
Section: Resultsmentioning
confidence: 99%
“…The observed enantioselectivity could be explained by the mechanism proposed for Ru-catalyzed transfer hydrogenations using amino alcohol ligands. [16,25] According to this mechanism, a ruthenium hydride and a proton from the ligand is simultaneously transferred from the catalyst to the prochiral carbonyl group. The structures of the two possible diastereomeric transition states were calculated using the Jaguar program.…”
Section: Resultsmentioning
confidence: 99%
“…We showed earlier that a remote dimethyl dioxolane structure on 2-azanorbornyl methanol causes a significant increase in the activity of the catalyst [13]. If the positive effect of this modification was transferable to a ligand with a (R)-methyl substituent at the carbinol carbon, we would obtain an extremely efficient catalyst.…”
Section: Ruthenium-catalyzed Transfer Hydrogenation Of Ketonesmentioning
confidence: 95%